The world’s largest social science infrastructure and academic survey research program: The World Values Survey in the New Independent States - C Haerpfer; K Aleksandrovna Kizilova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
The World Values Survey (WVS) is an international research program developed to assess the impact of values stability or change over time on the social, political and economic development of countries and societies. It started in 1981 by Ronald Inglehart and his team, since then has involved more than 100 world societies and turned into the largest non-commercial cross-national empirical time-series investigation of human beliefs and values ever executed on a global scale. The article consists of a few sections differing by the focus. The authors begin with the description of survey methodology and organization management that both ensure cross-national and cross-regional comparative character of the study (the survey is implemented using the same questionnaire, a face-to-face mode of interviews, and the same sample type in every country). The next part of the article presents a short overview of the project history and comparative surveys’ time-series (so called “waves” - periods between two and four years long during which collection of data in several dozens of countries using one same questionnaire is taking place; such waves are conducted every five years). Here the authors describe every wave of the WVS mentioning coordination and management activities that were determined by the extension of the project thematically and geographically. After that the authors identify the key features of the WVS in the New Independent States and mention some of the results of the study conducted in NIS countries in 1990-2014, such as high level of uncertainty in the choice of ideological preferences; rapid growth of declared religiosity; observed gap between the declared values and actual facts of social life, etc. The final section of the article summarizes the findings and key publications of the project for its data is widely used to analyse economic and political development, religious beliefs, gender equality, social capital, subjective well-being and many other issues of social development and values change in the world.